Development of an efficient retrotransposon-based fingerprinting method for rapid pea variety identification - Smýkal, Petr (Journal of applied genetics, 2006)
Fast and efficient DNA fingerprinting of crop cultivars and individuals is frequently used in both theoretical population genetics and in practical breeding. Numerous DNA marker technologies exist and the ratio of speed, cost and accuracy are of importance. Therefore even in species where highly accurate and polymorphic marker systems are available, such as microsatellite SSR (simple sequence repeats), also alternative methods may be of interest. Thanks to their high abundance and ubiquity, temporary mobile retrotransposable elements come into recent focus. Their properties, such as genome wide distribution and well-defined origin of individual insertions by descent, predetermine them for use as molecular markers. In this study, several Ty3-gypsy type retrotransposons have been developed and adopted for the inter-retrotransposon amplified polymorphism (IRAP) method, which is suitable for fast and efficient pea cultivar fingerprinting. The method can easily distinguish even between genetically closely related pea cultivars and provide high polymorphic information content (PIC) in a single PCR analysis.
Keywords: shluková analýza; DNA Primers; Electrophoresis, Polyacrylamide Gel; Polymorphism, Genetic; DNA Fingerprinting; hrách setý; retroelementy; Breeding; Cluster Analysis; chov; DNA primery; Česká republika; elektroforéza v polyakrylamidovém gelu; Pisum sativum; Retroelements; polymorfismus genetický; DNA fingerprinting; Czech Republic